2015
DOI: 10.1210/jc.2014-3647
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patients With Multifocal Papillary Thyroid Cancer Have Higher Recurrence Rates Than Adult Patients: A Retrospective Analysis of a Large Pediatric Thyroid Cancer Cohort Over 33 Years

Abstract: The pathological characteristics and recurrence rates of pediatric thyroid cancer have not changed over 33 years. Although younger patients present with more advanced disease, multifocality rather than age at diagnosis predicted recurrence. Recurrence was higher in pediatric than adult patients with multifocal papillary thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
48
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 37 publications
13
48
2
2
Order By: Relevance
“…Contrary to other reports, our data indicate that multifocality, or size, gender do not predict outcome. Multifocality, which is more frequent in paediatric than in adult patients, has been considered a risk factor for recurrence in some but not all studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to other reports, our data indicate that multifocality, or size, gender do not predict outcome. Multifocality, which is more frequent in paediatric than in adult patients, has been considered a risk factor for recurrence in some but not all studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In our series, the subgroup aged 10–14.9 years had the highest rate of persistent/recurrent disease in comparison to the other age subgroups; however, the small number of children aged <10 years might have influenced this result. Although younger age at diagnosis is associated with an advanced disease at presentation, these very young patients have a high rate of good response to treatment. The good response to therapy in younger subjects might be the consequence of high expression in thyroid cells of proteins such as the sodium/iodine symporter that may be involved in the excellent response to 131 I therapy .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multifocality is a predictor of aggressiveness such as intrathyroidal metastasis or disease recurrence. 39 , 40 Supporting this idea, we found that a gene set related to the cell cycle was coordinately enriched in high FAL1 expression group and that 3 genes from this set, namely, E2F1 , E2F2 , and VEGFA , were up-regulated in our PTC samples. Moreover, PTC with high E2F1 expression showed coordinately up-regulated expression of genes located on Chromosome 1q21 expression, suggesting 1q amplification might be related to high E2F1 expression.…”
Section: Discussionsupporting
confidence: 63%
“…According to this analysis, we can infer that the DRS system is more useful to predict recurrence in pediatric patients with DTC. Similar to previous studies, our results also showed that tumor size (>1 cm) and N stage (N1b) were predictors for recurrence [ 28 29 ].…”
Section: Discussionsupporting
confidence: 91%